2009
DOI: 10.1007/s00415-009-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

“Vestibular migraine”: effects of prophylactic therapy with various drugs

Abstract: Vertigo is frequently associated with migraine, and sometimes it is the cardinal symptom. This type of migraine is called "vestibular migraine", "migrainous vertigo", or "migraine-associated vertigo". Earlier findings on effective prophylactic medication for such migraine attacks and their clinical features are few and insufficient. Our aim was to study the influence of prophylactic therapy on this type of migraine and to specify its clinical features. In a retrospective approach 100 patients (median age 47 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 14 publications
3
56
0
5
Order By: Relevance
“…Medications used were beta-blocker, 49 patients, metoprolol (median dose 150 mg) or propranolol (median dose 160 mg), valproic acid, 6 patients (median dose 600 mg), topiramate, 6 patients (median dose 50 mg), butterbur extract, 4 patients (median dose 50 mg), lamotrigine, 3 patients (median dose 75 mg), amitriptyline 2 patients (75 to 100 mg), flunarizine, 1 patient (5 mg), and magnesium 3 patients (median dose 400 mg). The group without prophylactic therapy showed a reduction of vertigo intensity only 54 . An ongoing trial will test the efficacy of metoprolol in vestibular migraine (Prophylactic treatment of vestibular migraine with metoprolol -PROVEMIG trial) 55 .…”
mentioning
confidence: 91%
“…Medications used were beta-blocker, 49 patients, metoprolol (median dose 150 mg) or propranolol (median dose 160 mg), valproic acid, 6 patients (median dose 600 mg), topiramate, 6 patients (median dose 50 mg), butterbur extract, 4 patients (median dose 50 mg), lamotrigine, 3 patients (median dose 75 mg), amitriptyline 2 patients (75 to 100 mg), flunarizine, 1 patient (5 mg), and magnesium 3 patients (median dose 400 mg). The group without prophylactic therapy showed a reduction of vertigo intensity only 54 . An ongoing trial will test the efficacy of metoprolol in vestibular migraine (Prophylactic treatment of vestibular migraine with metoprolol -PROVEMIG trial) 55 .…”
mentioning
confidence: 91%
“…Gurkov et al [7] says that Neuhauser et al [13] diagnostic criteria present a broad base as a starting point to help clinicians guide themselves. Neuhauser & Lempert [1] report that the pathophysiology of MV is still unclear, none of the possible pathophysiological mechanisms for MV have been investigated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Baier et al [13] performed myogenic evoked potential (VEMP's) in patients with defined MV and in patients with probable MV. It was concluded that patients with vestibular migraine have low amplitudes on both sides (left and right) when compared to healthy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomisierte kontrollierte Studien zur Wirksamkeit von Medikamenten bei der vestibulären Migräne liegen allerdings bislang nicht vor. In einer retrospektiven Studie konnte der günstige Effekt der medikamentösen Prophylaxe nachgewiesen werden [20]. In prospektiven Studien über die Dauer von 1 Jahr fällt eine hohe Komorbidität mit Angsterkrankungen und Depressionen auf, was bei der Therapie berücksichtigt werden sollte [21,22].…”
Section: Zentrale Vestibuläre Syndromeunclassified